Pendugaan heritabilitas rill (realized heritability) dan kemajuan genetik produksi telur itik mojosari - ignatius maria unggul abrianto; Luqman Hakim; V.M.A. Nurgiartiningsih (Faculty of Animal Science, Universitas Brawijaya, 2017)
This study aims were to estimate the value of genetic parameters of realized heritability and to estimate the value of genetic progress in 10 Mojosari duck lines selected for 4 generations on the first 3 months cumulative egg production. Individual egg production records on 10 lines comprising 980 ducks with details of 108 drakes and 872 female ducks were used as research material. The results showed: 1) The realized heritability value of 3 months cumulative egg production in each duck line was moderate approaching high; 2) The response to selection of 3 months cumulative egg production selection in each duck line ranged from 0.37 to 0.48 eggs; 3) Selection on 3 months cumulative egg production characteristics could be appointed to be one of the selection criteria, because realized heritability value was moderat close to high and the response to selection was positive.